2005
DOI: 10.1021/jm048982w
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Quantitative Structure−Activity Relationship Analyses of β-Lactam Antibiotics and Tripeptides as Substrates of the Mammalian H+/Peptide Cotransporter PEPT1

Abstract: The utilization of the membrane transport protein PEPT1 as a drug delivery system is a promising strategy to enhance the oral bioavailability of drugs. Since very little is known about the substrate binding site of PEPT1, computational methods are a meaningful tool to gain a more detailed insight into the structural requirements for substrates. Three-dimensional quantitative structure-activity relationship (3D-QSAR) studies using the comparative molecular similarity indices analysis (CoMSIA) method were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 32 publications
3
81
1
Order By: Relevance
“…This implies that the conformation adapted by the semi-rigid Met-Pro-Pro molecule was favourable for binding to hPEPT1 but unfavourable for translocation. Biegel et al have shown that Ile-Pro-Pro and Val-Pro-Pro have affinity constants of 0.28 and 0.06 mM, respectively (14), which was in accordance with X aa -Pro-Pro binding to hPEPT1 with high affinity. Whether these two tripeptides were transported by hPEPT1 was, however, not reported (14).…”
Section: Substrates and Inhibitors Of Hpept1mentioning
confidence: 55%
See 1 more Smart Citation
“…This implies that the conformation adapted by the semi-rigid Met-Pro-Pro molecule was favourable for binding to hPEPT1 but unfavourable for translocation. Biegel et al have shown that Ile-Pro-Pro and Val-Pro-Pro have affinity constants of 0.28 and 0.06 mM, respectively (14), which was in accordance with X aa -Pro-Pro binding to hPEPT1 with high affinity. Whether these two tripeptides were transported by hPEPT1 was, however, not reported (14).…”
Section: Substrates and Inhibitors Of Hpept1mentioning
confidence: 55%
“…Bailey et al reported a template for PEPT1 substrates, which identified four key binding regions in the PEPT1 binding site (13). Gebauer et al created a quantitative structure-activity relationship (QSAR) model on dipeptides, tripeptides and β-lactam antibiotics employing CoMSIA descriptors (14,15). A QSAR model that correlates the binding of tripeptides to hPEPT1 with the alignment independent VolSurf descriptors was reported in 2006 (16).…”
Section: Introductionmentioning
confidence: 99%
“…These transfected models add greatly to our knowledge and understanding of substrate specificity for a specific transporter. Information of substrate specificity can be further incorporated into computational modeling which may aid in the design of better substrate or inhibitor drug molecules to increase the bioavailability (Schwab et al, 2003;Biegel et al, 2005;Ungell, 2004). Structural requirements for only a few transporter systems have been identified like PePT1 (Biegel et al, 2005) and P-gp (Ekins et al, 2002;Schwab et al, 2003;Ungell, 2004).…”
Section: Transfected Mdck Cell Linesmentioning
confidence: 99%
“…The effort for unravelling structural elements of the di-/ tripeptides important for binding and translocation by hPEPT1 have resulted in a few quantitative structure-affinity relationship models. [12][13][14][15] It is generally accepted that the transporter has a preference for di-and tripeptides composed of l-configured amino acids with the peptide bonds in a trans-conformation. A free amino group in the N-terminal seems to be important whereas a free carboxylic acid in the C-terminal is not an absolute prerequisite.…”
Section: Introductionmentioning
confidence: 99%